Implementasi Website Sebagai Sarana Pemasaran dan Informasi pada PT. Kurnia Putra Maduma - Yudhistira Adhitya Pratama; Ade Maulana; Asima Manurung; Normalina Napitupulu (Yayasan Literasi Sains Indonesia, 2024)
PT. Kurnia Putra Maduma (KPM) is an electrical contractor company that provides high-quality solutions in Indonesia. Despite offering superior services, KPM faces challenges in providing easy access to information for customers. This community service project was conducted at the headquarters of PT. Kurnia Putra Maduma at Jl. Jaya II No. 23A, Sudirejo II, Medan City, North Sumatra, from April 2024 to May 2024, with the goal of developing a website to improve information access for customers and enhance company communication efficiency. The project stages included planning, where the development team collaborated with KPM staff to identify needs and determine the website design; website development based on feedback from the planning phase; testing and evaluation to ensure the website functions as expected; and staff training in the use and maintenance of the website. The results of this project show that the developed website successfully provided easier information access for customers and supported more efficient communication. The website features an organized structure, responsive design, and performs well across various devices and browsers. Staff training also effectively ensured their ability to manage and update content independently. In conclusion, the website successfully addressed the information access challenges at PT. Kurnia Putra Maduma and supported the company's communication efficiency. Recommendations include regular content updates, SEO optimization, performance monitoring, enhanced security.